Multithreaded Scalable Matching Algorithm For Intrusion Detection Systems - Hnaif, Adnan Ahmad Abdelfattah (2010)

(untitled)
The increasing speed of today’s computer networks directly affects the performance of Network Intrusion Detection Systems (NIDS) in terms of speed of detection of threats. Therefore, the performance of the existing algorithms needs to be improved both in sequential and parallel to enhance the speed of the detection engine used in SNORT-NIDS. Hence, this thesis defines a new algorithm called the Distributed Packet Header Matching algorithm (DPHM), and a New Network Intrusion Detection Systems (NNIDS) platform using hybrid technology in order to increase the overall performance of SNORT-NIDS.